2017
DOI: 10.1007/s10533-017-0303-3
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in heathland soil labile organic carbon under future atmospheric and climatic conditions

Abstract: The NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 74 publications
(127 reference statements)
2
11
0
Order By: Relevance
“…Elevated CO 2 has been found to increase plant C/N ratios (Larsen et al 2011;Arndal et al 2013), root growth (Arndal et al 2013(Arndal et al , 2014, and the belowground plant N stock (Arndal et al 2013), suggesting enhanced plant N demand and uptake. Nitrogen stocks in the light soil density fraction were significantly reduced (Thaysen et al 2017), whereas extractable soil N pools remained constant (Larsen et al 2011), and gross N mineralization rates were constant or even enhanced (Larsen et al 2011;Björsne et al 2014). Based on these findings, we hypothesize that elevated CO 2 had stimulated gross protein depolymerization rates that provided additional N for plant uptake without reducing N availability for soil microorganisms, resulting in constant or enhanced gross N mineralization rates.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…Elevated CO 2 has been found to increase plant C/N ratios (Larsen et al 2011;Arndal et al 2013), root growth (Arndal et al 2013(Arndal et al , 2014, and the belowground plant N stock (Arndal et al 2013), suggesting enhanced plant N demand and uptake. Nitrogen stocks in the light soil density fraction were significantly reduced (Thaysen et al 2017), whereas extractable soil N pools remained constant (Larsen et al 2011), and gross N mineralization rates were constant or even enhanced (Larsen et al 2011;Björsne et al 2014). Based on these findings, we hypothesize that elevated CO 2 had stimulated gross protein depolymerization rates that provided additional N for plant uptake without reducing N availability for soil microorganisms, resulting in constant or enhanced gross N mineralization rates.…”
Section: Introductionmentioning
confidence: 83%
“…In combination, elevated CO 2 , warming, and drought led to a deceleration of soil N turnover after the first two years of the experiment, with stronger single treatment than combined treatment effects (Larsen et al 2011). A more recent study after eight years, however, suggests significant N losses from the light soil fraction after longer exposure to the combined treatments (Thaysen et al 2017).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…By contrast, Gram-negative bacteria contain characteristics of copiotrophs, as they prefer labile carbon compounds and organic nitrogen ( Treseder et al, 2011 ), particularly in the form of plant root exudates ( Balasooriya et al, 2014 ); and indeed it has been observed that Gram-negative bacteria incorporated almost ten times as much plant-derived carbon as Gram-positive bacteria under well-watered conditions ( Fuchslueger et al, 2014 ). Under drought, labile organic carbon is increasingly scarce within soils ( Thaysen et al, 2017 ), and in turn the rate of transfer of plant-derived carbon to microbes has been observed to go down ( Ruehr et al, 2009 ), possibly as microbial communities switch to degrading more recalcitrant carbon sources within plant organic matter ( Bradford et al, 2008 ). Karst et al (2016) posited that plants close protein channels to prevent sugar transport to the rhizosphere as part of osmotic adjustment under drought.…”
Section: Potential Causes Of Soil Community Trends Under Droughtmentioning
confidence: 99%